Effects of interfacial layer-by-layer nanolayers on the stability of the Cu TSV: Diffusion barrier, adhesion, conformal coating, and mechanical property. (15th August 2018) - Jeong, Daekyun; Abdur, Rahim; Joo, Young-Chang; Jang, Jae-il; Cha, Pil Ryung; Kim, Jiyoung; Min, Kyeong-Sik; Lee, Jaegab
Abstract: The Through-Silicon (Si) Via (TSV) is the integration technology for three-dimensional integrated-circuit packaging. The layer-by-layer (LbL) technique has been used to deposit flexible poly(allylamine) hydrochloride (PAH)/polystyrene sulfonate (PSS) multilayers inside scalloped Si trenches of a high aspect ratio, fabricated by the Bosch-etching process. An outstanding control of the thickness and the conformality of the polymer layers, along with a significantly improved planarization, was achieved due to the LbL-technique self-termination effects. In addition, the basic properties of the polymer layers have been characterized: diffusion-barrier properties, adhesion, density, and elastic modulus. The results of this study demonstrate the feasibility of LbL multilayers regarding the TSV liner for the vertical interconnect accesses with a high aspect ratio of highly scalloped surface walls.